Sintesis CaTiO3 Berbasis Limbah Cangkang Telur Bebek Untuk Aplikasi Sel Surya - Muhammad, Al Jalali; Wa Ode Sitti Ilmawati; Aslan Ndita (ZETROEM, 2025)
Duck’s eggshell is one type of organic waste that has not been used optimally. Duck eggshell contain CaCO3 as a CaO source, so they are potentially processed as CaTiO3. The purpose of this study was to investigate the effect of sintering temperature on morphology, phase, functional groups, and optical properties of CaTiO3. The sintering temperatures were used in this research from 800oC, 900oC and 1000oC for 4 hours. SEM analysis show that there was the different of morphology properties to each samples. Homogeneity of CaTiO3 particles can be seen from spherical distribution of CaTiO3 particles, especially at 800oC. In this research was found orthorombic crystal structure of CaTiO3 to each sintering temperatures.According to the XRD patterns, it can be seen that there was a simillar patterns to each samples. Each peaks of CaTiO3 that formed on 2 (23,329o; 29,960o; 33,152o; 40,990o; 47,568o; and 49,211o) have the growth orientations respectively are (400), (510), (440), (444), (800), and (820). Particle size at sintering temperature of 800oC, 900oC and 1000oC respectively are 43,60438 nm, 33,43218 nm, and 29,35699 nm).